Characterization of blood-derived exosomal proteins after exercise. Issue 9 (September 2020) - Xiang, Hongkai; Chen, Shisheng; Zhou, Junhan; Guo, Junxiu; Zhou, Qingfeng; Zhou, Qishuang
Objective: To assess changes in plasma exosome levels and protein content in mice after long-term exercise. Methods: We subjected 9-month-old adult C57BL/6J mice to daily treadmill running exercise for 4 weeks prior to the isolation of blood-derived exosomes. Exosomal proteins were identified using mass spectrometry. Results: Extracellular bodies were successfully isolated from mouse blood. Protein levels were altered in blood-derived exosomes after chronic treadmill exercise. Levels of the secretagogue secretogranin 2 were markedly elevated in exercise-induced exosomes. Conclusion: Our data suggest that levels of secretogranin 2 were increased in mouse exosomes following chronic treadmill exercise. We conclude that exercise increases exocrine secretion of secretogranin 2.